Comparative Analysis of Information Retrieval Behavior of Scientific Bibliographic Databases Users - K. V. Monankov (Библиосфера, 2021)
Statistical study of the information retrieval behavior of information resources users, generated by Institute of Scientific Information on Social Sciences of RAN (INION RAN), in the search for scientific information over the past decade for two groups of users: guests and registered users, has been carried out. The results of the study are compared with that of the similar studies made in earlier periods to detect changes and trends. Comparative analysis showed a decrease in the search activity of users with the status of a guest, both in terms of the duration of the search session and the use of unique search operations, while the behavior of registered users has not changed. For the analysis, the following indicators were used: search session duration, number of unique operations per session, use of various databases and interfaces types. Such analysis of the information retrieval behavior is relevant for understanding effectiveness of information retrieval resources. The statistical data can be used to design new search interfaces for various categories of users.